PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN PADA RUMAH SAKIT THURSINA DI DURI - Manik, Sudarmin (Eko dan Bisnis: Riau Economic and Business Review, 2016)
The purpose of this study was to determine how much influence  the quality of service to patient satisfaction in hospital in Thursina Duri. The population in this study were hospital inpatients  in Thursina Duri which amounts to 100 people. Sampling was conduted using random sampling. Analysis of the data using reliability, clasisical assumptions, multiple liner regression, Uji_F and uji_t. test conducted to determine the relationship between independent variables and the dependent variable.Based on the research that the quality of service simultaneously influence the patient’s satisfactions with the value of correlation = 0.979 which shows the close relationship between service quality and patient satisfaction in hospital in Thursina Duri. While the persenrtase impact of service quality to satisfaction of patient at hospital in Thursina Duri. While adjusted square 0.957 obtained which means the quality of service has contributed of 95.7 persent to client satisfaction. As well as the positive and significant impact on patients satisfaction with the level of Sig.0.000.The conclusion from this study that hypothesis simultaneously and partially between the variable quality of service to the patient’s satisfaction is proven and can be accepted as true